Development of a ‘drop-count’ method for the screening of the ethanol content in hand sanitisers using oxalic acid and potassium permanganate titrimetry - Monts’o, Kaneoa E.; Ts’emane , Rapelang; Mpakanyane , Teboho E.; Masiloane-Bohloko, Selloane C.; Ramashamole , Thato V.; George, Mosotho (Orapuh Journal, 2022)
IntroductionThe demand for ethanol-based sanitisers has increased dramatically since the dawn of the COVID-19 era, making it very difficult for health regulators to ensure the quality of the products and the safety of unsuspecting consumers. This article reports the development and application of a simple 'drop-count' titrimetry method for the determination of ethanol in hand sanitisers. Materials and Methods This method follows the classical potassium permanganate-oxalic acid titrimetry but uses very small volumes of the reagents – 0.5 mL of ethanol sample solution, 6 mL of acidified 0.1 M potassium permanganate, and a few counted drops of 0.1M oxalic acid. ResultsThis method achieved satisfactory figures of merit, namely, linearity (R2 ≥ 0.9667), reproducibility, and importantly very little matrix effect in the alcohol concentration range of 50 to 80%. Conclusion The small volumes (< 10 mL in total) of the reagents required make this method considerably safe and cost-effective and applicable for fieldwork even by untrained personnel, not just chemists as is often the case for field applications.